Internalisasi Nilai Kebudayaan Lokal Bugis (Sipakatau, Sipakalebbi, dan Sipakainge) - Vikriatuz Zahro; Reni Putri Anggraeni; Vicko Taniady (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2020)
Character education is the primary weapon to form good quality students. However, the digital era's entry does not always have a positive impact, especially for students in Indonesia. The growth of individualistic attitudes, bullying behavior, lack of manners, and so on positively impact creating ethical and moral young generations. This is an urgency that must be addressed wisely in education to form a new character education model for students in Indonesia. Internalization of local-Bugis cultural values ​​is an urgency that must apply in the world of character education in Indonesia. The research method used in this research is a qualitative descriptive method using secondary data and a case study approach to the adverse effects of the digital era for students in Indonesia. This study's results indicate that the local value of Bugis, which is reflected through Sipakatau, Sipakalebbi, and Sipakainge, will positively impact the character development of students in Indonesia. So that in the end, based on these local Bugis values, it is hoped that students will be able to improve ethics and other behaviors for the better.